Metastasis Research Protocols - Brooks, Susan A.; Brooks, Susan A.; Schumacher, Udo.; Schumacher, Udo. (Methods in Molecular Medicine,, 2001)
Although ninety percent of fatal cancer cases involve the spread of a primary tumor, the formation of metastases is still a poorly understood, complex process and a significant problem in the treatment of cancer patients. In Metastasis Research Protocols, leading international investigators describe the key methods needed to investigate why and how metastasis occurs. Volume I of this two-volume set, Analysis of Cells and Tissues, presents a comprehensive collection of established and leading-edge techniques for analyzing the expression of key molecules and for examining their production at the genetic level. The work focuses on the analysis and mapping of molecules produced by cells and tissues, and on the molecular biology underlying their expression. The traditional methods range from the histopathological and the immunocytochemical to SDS-PAGE, Western blotting, and enzyme zymography. Newer and more specialized techniques for analyzing the genetic aspects of metastasis include in situ hybridization to localize mRNAs, FISH, CGH, methylation analysis of CpG islands, RT-PCR, and differential display. The second volume of this set, Analysis of Cell Behavior In Vitro and In Vivo, moves to the level of living cells and tissues to present methodologies applicable to examining metastatic behavior in vitro and in the whole animal. Comprehensive and authoritative, the two volumes of Metastasis Research Protocols constitute a gold-standard collection of readily reproducible methods for understanding the metastatic cascade-first at the cellular and molecular levels, then at the level of the whole organism-responsible for the spread of cancer and for developing novel strategies to combat its spread.